Expression of Peroxiredoxin 2 and Vascular Endothelial Growth Factor Receptor 2 in Pterygium. Issue 7 (July 2017) - Wang, Yuchuan; Lin, Jinyong; Chen, Luxia; Wang, Liming; Hao, Peng; Han, Ruifang; Ying, Ming; Li, Xuan
Abstract : Purpose: The expression of peroxiredoxin 2 and vascular endothelial growth factor receptor 2 (VEGFR2) was detected in pterygium to investigate whether they are involved in the pathogenesis or recurrence of pterygium and to evaluate the association between peroxiredoxin 2 and VEGFR2 in pterygium. Methods: Ten normal bulbar conjunctivae, 35 primary pterygia, and 35 recurrent pterygia were obtained. Formalin-fixed, paraffin-wax–embedded tissues were analyzed by immunohistochemistry with peroxiredoxin 2 and VEGFR2 antibodies. Results: There was no statistical difference between primary pterygia and recurrent pterygia in terms of age and sex ( P = 0.685; P = 0.811). The expression rate of peroxiredoxin 2 (94.3%, 66/70) and VEGFR2 (61.4%, 43/70) was increased in pterygia compared with normal conjunctivae (negative). The expression of peroxiredoxin 2 in recurrent pterygia (negative 0, weak 0, moderate 27, strong 8) was higher than that in primary pterygia (negative 6, weak 16, moderate 13, strong 0) ( P < 0.001). The expression of VEGFR2 in recurrent pterygia (negative 4, weak 5, moderate 12, strong 4) was higher than that in primary pterygia (negative 23, weak 10, moderate 1, strong 1) ( P < 0.001). The expression of peroxiredoxin 2 was consistent with that of VEGFR2 in pterygium ( r = 0.348, P = 0.006). Conclusions: Overexpression of peroxiredoxin 2 and VEGFR2 in pterygium might be involved in the pathogenesis or recurrence of pterygium. The increase of VEGFR2 might be related to the increase of peroxiredoxin 2 in response to excessive reactive oxygen species from ultraviolet exposure.